STRATEGI PENGUATAN AKHLAK ISLAMI PADA ANAK USIA DINI - Salman Zahidi (Universitas Islam Lamongan, 2017)
The cultivation of Islamic moral values in early childhood Islamic education is a very important component. The strengthening of early childhood morality is one of the efforts to lay the foundation of moral development dimension which is expected to influence other development aspects, especially the socio-emotional development and spiritual intelligence of early childhood. Therefore, good strategies are needed in culticating and strengthening the students themselves. The strategies of cultivating moral values could affect the level of awareness of a person in understanding and implementing Islamic moral values. At an early age the sense of vision is more dominant than the sense of hearing, then a child will more absorb and imitate the behaviors of a teacher, so the teacher's exemplary will be more effective in strengthening early childhood education. The teacher's exemplary is the cultivation and at the same time the strengthening of noble values in each child.